Assessments of the Growth Rate of Siberian larch (Larix sibirica Ledeb.) and its distribution in Mongolian Altai Mountain Range - P, Battulga; J, Tsogtbaatar; S, Gerelbaatar (Proceedings of the Mongolian Academy of Sciences, 2018)
The Mongolian Altai mountain range stretches from east to west for more than 800 kilometers, and its forest cover is considered the southwestern boundary of the distribution of Mongolian forests and is characterized by a unique combination of high-mountain and desert ecosystems. Siberian larch (Larix sibirica Ledeb.) is one of the main forest-forming tree species in the Mongolian Altai and covers 112.0 thousand ha of area and is distributed at an altitude of 2300 to 2700 m a.s.l. In this study, we attempted a comparative study of tree growth rates in larch forests, which are associated with four different altitudinal zones in the Mongolian Altai, aimed at determinining the lower and upper limits of forest distribution in this region. We used the natural quantitative indicators in this study. We carried out the diameter growth rate analyses on 15 model tree samples taken from the Mongolian Altai and 4 samples from Central Khangai regions. All the trees were divided into fast-growing and slow-growing. The results of the assessments showed that 60 percent of the studied forests belonged to slow-growing forests. Slowest growth rate was observed in the forests of Khan Taishir and Khar Azarga mountains, which are the southernmost tip of conifer forest distribution in Mongolia. For the first time in Mongolia we observed that the upper limit of larch forests reached up to 2700 m a.s.l. Such slow rate of tree growth in larch forests is the result of the existing harsh continental climate, aridity, and high altitudinal distribution in the Mongolian Altai. Our findings can become the scientific basis for the development of a sustainable forest management plan in the forests of the Mongol Altai, taking into account the different growth rate between stands.